An Adaptable Aesthetic: Theodor Sparkuhl's Contribution to Late Silent and Early Sound Film-making at British International Pictures, 1929–30. Issue 2 (April 2020) - Robinson, Kelly
Abstract : The German cinematographer Theodor Sparkuhl worked at Elstree from 1929 to 1930. Accounts of this period in Britain have often emphasised the detrimental effects of the arrival of the sound film in 1928, how it sounded the death knell of film as an international medium and how the film industry struggled to adapt (economically, technically, aesthetically). However, this article shows that the international dimension of the film industry did not disappear with the coming of sound and British International Pictures (BIP) was an exception to what Robert Murphy has called the 'catalogue of failure' during this turbulent period in British film history. Sparkuhl indisputably contributed to this achievement, working as he did on eight feature films in just two years from around July 1928 to April 1930, as well as directing several BIP shorts. Sparkuhl's career embodies the international nature of the film industry in the 1920s and 1930s. In Germany he moved within very different production contexts, from newsreels to Ufa and the Großfilme ; in Britain from big-budget films aimed at the international market to low-scale inexpensive films at BIP. As what Thomas Elsaesser has called an 'international adventurer', Sparkuhl cannot be contained within any single national cinema history. The ease with which he slipped in and out of different production contexts demonstrates not just his ability to adapt but also the fluidity between the different national industries during this period. In this transitional phase in Britain, Sparkuhl worked on silent, part sound and wholly sound films, on films aimed at both the international and the indigenous market, and in genres such as the musical, the war film and comedy. The example of Sparkuhl shows that German cameramen were employed not only for their aesthetic prowess but also for their efficiency and adaptability.